2018
DOI: 10.20546/ijcmas.2018.711.244
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Evaluation of Maize Hybrid Germplasm Lines for Drought Tolerance under Receding Soil Moisture Conditions

Abstract: Maize, (Zea mays L.) is the third most important cereal food crop consumed by the world"s population after wheat and rice. It is a versatile crop grown under different agroclimatic conditions.Owing to its genetic yield potential maize is referred as "queen of cereals". It is grown throughout the year in all the seasons in India but predominantly grown as a kharif crop and accounts approximately 9 percent of the total food grain production of the country. Maize plays an important role in Indian economy, besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…[ 19 ] reported the effects of stress on proline accumulation in corn variety and interaction was found significant. The study on the drought tolerance in 12 corn hybrids observed that increased proline content and wax content in the drought tolerance corn hybrids under moisture stress and suggested to use these parameters as most reliable parameters for the phenotypic drought tolerant screening [ 20 ]. Therefore, the drought tolerant cultivars in corn can be developed by the introgression of these mechanisms in the elite inbreds and combining them in hybrids cultivars through genetical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] reported the effects of stress on proline accumulation in corn variety and interaction was found significant. The study on the drought tolerance in 12 corn hybrids observed that increased proline content and wax content in the drought tolerance corn hybrids under moisture stress and suggested to use these parameters as most reliable parameters for the phenotypic drought tolerant screening [ 20 ]. Therefore, the drought tolerant cultivars in corn can be developed by the introgression of these mechanisms in the elite inbreds and combining them in hybrids cultivars through genetical approaches.…”
Section: Introductionmentioning
confidence: 99%